Salmonella risk in poultry meat - Tonbak, Fadime; Atasever, Mustafa; Çalicio?lu, Mehmet (Ataturk Universitesi, 2017)
Poultry meat which has an economic importance and high nutritional value among animal protein sources has an important role in supplying the food needs. Owing to the nutrients they contain, poultry meats create an environment which is quite suitable for the growth of pathogenic and apathogenic microorganisms. Salmonella spp. are among the significant pathogens causing problems on animal health, public health and food safety with high morbidity and mortality worldwide. In terms of public health, the extent of losses caused by these agents has been expressed as billions due to the increased infection prevalence, development of multidrug antimicrobial resistance, decreased food supply, labor intensity and treatment costs. The epidemiology of Salmonella agents is rather complex thank to the widespread distribution of host-nonspecific serovars without showing any clinical signs of disease. Therefore, they pose potential risks on food safety from farm to fork. In world, some efforts have been made to decrease Salmonella prevalence in poultry flocks and products by employing various control and eradication strategies. However, fighting againstSalmonella requires a comprehensive and complex study and, it may be minimized by applying strict monitoring at all stages of production chain and taking necessary precautions rigorously. The purpose of this review was to present valuable information about microbiology, classification, serotypes, antigenic structure, virulence factors, resistance mechanisms to environmental conditions, infections concerning public and poultry health, prevalence and control measures of Salmonella species.
Kanatli Etlerinde Salmonella Riski
Keywords: Poultry meat; Public health; Salmonella risk